Tree of Me: A Nature-Based Intervention for Patients, Professionals, and Learners - Douglas, Stephen; Trull, Melissa; Slusarz, Claire (Journal of pain and symptom management, 2025)
1. Articulate how the experience-reflect-share framework may apply in their own practice. 2. Utilize creativity to deepen their listening skills and explore their own sources of meaning-making and connection. Nature has the capacity to connect us to our bodies and stories. This presentation shares a nature-based, story-telling project designed for patients, healthcare professionals and learners, which serves as a therapeutic intervention and assessment tool. Serious illness can disrupt our sense of self and place in the world. For many, in addition to its positive physical and emotional impacts, nature is a primary source of meaning and connection. (1–4) Accessing nature can be difficult when ill. This presentation shares a nature-based intervention for patients and healthcare workers, using nature as a frame for exploration. Drawing on Narrative Medicine pedagogy and mindfulness practices, this presentation offers participants a chance to reflect on their own sources of connection and meaning, and how these resources impact patient interactions. (5,6) We will discuss the experience-reflect-share framework and how this can be adapted to participants’ clinical and educational settings. Participants will: • Explore their own sources of meaning-making and connection • Further develop listening skills through creativity • Articulate how the experience-reflect-share framework may apply in their own practice Methodology and Discussion: Attendees will be guided through the intervention in three stages, beginning with a mindfulness practice centered around pieces selected from nature. Participants then incorporate these pieces into a book-making project, reflecting on their stories through art and writing. Finally, participants are invited to share their reflections. We will discuss the results we have achieved implementing this intervention with patients and learners, and how the experience-reflect-share framework may be adapted. For many, time in nature offers perspective, context and meaning. Opportunities to engage in nature in the setting of serious illness can often be compromised. This guided experience of nature offers an opportunity for self-reflection and connection, eliciting goals and values and fostering feeling seen and heard. For caregivers, who are subject to similar abstracting forces, this intervention can aid in spiritual self-assessment and resiliency. 1. Lackey NQ, Tysor DA, McNay GD, Joyner L, Baker KH, Hodge C. Mental health benefits of nature-based recreation: a systematic review. Ann Leis Res. 2021;24(3):379-393. doi:10.1080/11745398.2019.1655459 2. Bratman GN, Hamilton JP, Daily GC. The impacts of nature experience on human cognitive function and mental health. Ann N Y Acad Sci. 2012;1249(1):118-136. doi:10.1111/j.1749-6632.2011.06400.x 3. Tillmann S, Tobin D, Avison W, Gilliland J. Mental health benefits of interactions with nature in children and teenagers: a systematic review. J Epidemiol Community Health. 2018;72(10):958-966. doi:10.1136/jech-2018-210436 4. Martin L, White MP, Hunt A, Richardson M, Pahl S, Burt J. Nature contact, nature connectedness and associations with health, wellbeing and pro-environmental behaviours. J Environ Psychol. 2020;68:101389. doi:10.1016/j.jenvp.2020.101389 5. Milota MM, van Thiel GJMW, van Delden JJM. Narrative medicine as a medical education tool: A systematic review. Med Teach. 2019;41(7):802-810. doi:10.1080/0142159X.2019.1584274 6. Remein CD, Childs E, Pasco JC, et al. Content and outcomes of narrative medicine programmes: a systematic review of the literature through 2019. BMJ Open. 2020;10(1):e031568. doi:10.1136/bmjopen-2019-031568